Responsibility to Protect Pemerintah Laos Mengatasi Masalah Pendidikan Melalui Program Education for All dari UNESCO Tahun 2003-2015 - Ardianti, Dwi Juni; Sushanti, Sukma; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2018), 2018)
ABSTRACT   Human resources issue in Lao PDR is a complex issue, such as less attention from government, unwilling children to go to school, unskilled teachers to inaccessible and uneven access of education. Responsibility to protect of Lao PDR government in dealing with education issue is in a form of implementing Education for All (EFA) programs of UNESCO in 2003-2015. This research aims to analyze the implementation of Education for All (EFA) programs by Lao PDR government. The concept of human security is able to explain the importance of education through the process of how the government captures this as a threat to the individual and the responsibility to protect (RTPR) from Lao PDR government. Since the collaboration with UNESCO, the Lao PDR government has finally directed its national policy to be focused on education This research uses descriptive qualitative method using official documents issued by Lao PDR government and UNESCO data.   Keywords : Lao PDR, Education for All, Human Security, Responsibility to Protect (RTPR)